Perch and litter preferences in chicks - Bramgaard Kjaersgaard Nielsen, Cecilie (2018)
There is a lack of research on the litter and perch preferences of chicks during the first three weeks of their lives. The purpose of this study was to identify which perch and litter types the chicks preferred, if their preference changes over time and if the preference of litter types change depending on the specific behaviours. First a pilot study was made to find out which different litter and perch types should be used. After that an experiment was carried out over three weeks with six different litters and six different perches to see which they preferred. For this study 94 LSL (Lohman selected leghorn) classic were used, they arrived at the research facility on the same day they were hatched. The different litters compared were; straw, sand, peat, wood shavings, hemp and crushed straw pellets. The different perches compared were a large rope, a small rope, a small flat, a large flat, a small round and a large round perch. The chicks had access to three different litter and perch types at a time, and they were changed every Monday, Wednesday and Friday. The result showed that the chicks overall had a preference for wood shavings, hemp and straw, the preferred litter types for preening and sleeping/resting was the same. For picking they preferred wood shavings, hemp and sand. The preferred litter types for dustbathing were sand and peat. The overall result for their perch preferences showed that they had a preference for the small flat, the large flat and the large rope. The most preferred perch types for preening was the large round, the small flat and the large flat perch. For sleeping and resting they preferred the small rope, the large rope, the small round and the large flat perch.